2006
DOI: 10.1063/1.2354574
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent wave interference and the total transparency of a warm high-density plasma slab

Abstract: It is shown that an overcritical density plasma slab can be totally transparent to a p-polarized obliquely incident electromagnetic wave. High transparency is achieved due to the interference of the evanescent waves in the subcritical region. The transmission coefficient has the resonant character due to the excitation of a plasma surface mode (plasmon-polariton). It is crucial that two evanescent waves have certain phase shift to provide non-zero energy flux through non-transparent region. The required phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…They restricted their attentions to electrostatic surface waves on cold cylindrical plasma columns. The effect of a finite temperature on the dispersion relation of electrostatic surface waves was studied by Ritchie (1963), who applied a simple hydrodynamical model, and Guernsey (1969), who adopted the kinetic theory. Vedenov provided a general dispersion relation without limiting to electrostatic approximation, which showed that in cold plasma half-space, surface plasma polaritons existed with frequencies ranging from ω spps → ω P / √ 2 down to ω spps = 0 (Vedenov 1965).…”
mentioning
confidence: 99%
“…They restricted their attentions to electrostatic surface waves on cold cylindrical plasma columns. The effect of a finite temperature on the dispersion relation of electrostatic surface waves was studied by Ritchie (1963), who applied a simple hydrodynamical model, and Guernsey (1969), who adopted the kinetic theory. Vedenov provided a general dispersion relation without limiting to electrostatic approximation, which showed that in cold plasma half-space, surface plasma polaritons existed with frequencies ranging from ω spps → ω P / √ 2 down to ω spps = 0 (Vedenov 1965).…”
mentioning
confidence: 99%
“…Matching of the evanescent solutions with the incident vacuum wave (at the other side of the negative ǫ region) shows that the total transmission may be obtained only when the transition layer with ǫ > 0 is included [11]. The condition of the absolute transparency is equivalent to the resonant condition for the excitation of the surface plasma mode.…”
Section: Evanescent Wave Interference and The Energy Transportmentioning
confidence: 97%
“…In this case, the resonant excitation of surface modes by the incident light can be achieved via the presence of a single transition layer with 0 < ǫ < 1 on one side of the slab with ǫ < 0 [11]. The superposition of two evanescent waves provides a finite energy flux through the region with ǫ < 0, which is equal to that in the incident electromagnetic wave.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the effects of surface wave plasmons on reflection and guiding properties of multi-layer structures were analyzed in [17][18][19][20]. Resonant transmission has also been studied theoretically in earlier works [10,[21][22][23]. Tunneling phenomena in general remain to be of great interest and subject of controversies in quantum mechanics [24,25] and the results of this paper are relevant to quantum mechanical resonant tunneling.…”
Section: Introductionmentioning
confidence: 99%